Treatment of cervical dystonia with botulinum toxin in a patient with myasthenia gravis - MARCIA RUBIA R. GONÇALVES; EGBERTO R. BARBOSA; ANTONIO A. ZAMBON; PAULO E. MARCHIORI (Arquivos de Neuro-Psiquiatria)
We report the case of a 49-year-old woman who has the rare combination of myasthenia gravis and cervical dystonia. She was treated with botulinum toxin type A with good response and no evidence of deterioration of the myasthenic symptoms. We therefore conclude that it is possible to use botulinum toxin in the presence of defective neuromuscular transmission.